Law Production in Multiparty Presidentialism: Veto Player Theory and its Application to Korea - Moon, Woojin (Journal of East Asian Studies, 2022)
In this article, I offer a theory of lawmaking in multiparty presidential systems with different legislative institutions. I present a model that combines Krehbiel's pivotal politics theory with Tsebelis's veto players theory. This model simplifies various institutional veto players into the de facto veto players. I analyze the model to explain how the government type (unified versus divided governments), the legislative rules (majoritarian versus supermajoritarian rules), and the party system (two-party versus multiparty systems) affect legislative productivity. I apply the theoretical results obtained to solve the puzzle about the nondifferential legislative performance between unified and divided governments in the National Assembly. I test a hypothesis stating that the distance between the ideological positions of the agenda-setter and the de facto veto players has a negative effect on the proportion of controversial bills enacted between the 16th and the early 21st National Assemblies.
Keywords: government types; law production; legislative rules; multiparty presidentialism; party system; veto player theory